Development and validation of a genre-based second language (L2) writing self-efficacy scale - Zhang, Jianhua; Zhang, Lawrence Jun; Zhu, Ye (Frontiers in Psychology, 2023)
Writing self-efficacy serves as one of the essential motivational factors in L1 and L2 writing, which has been measured by a series of scales in L1 and L2 contexts. However, the issue of task specificity was not resolved appropriately. This study aims to tackle this issue by entailing the genre characteristics of L2 writing tasks through developing a genre-based L2 writing self-efficacy scale with pertinent items. The new scale was designed with reference to the available research into writing self-efficacy. Its factorial structure was examined by structural equation modeling. Convergent validity and discriminant validity of the scale were examined by taking into consideration the average variance extracted and composite reliability for each individual factor involved in the scale, whereas the predictive validity of the scale was computed through regression analysis. Results show that the genre-based L2 writing self-efficacy scale demonstrated sound psychometric qualities. Theoretical and pedagogical implications of these research findings are discussed.